Pengembangan Manajemen Sumber Daya Manusia di Lembaga Pendidikan Islam - Ramdanil Mubarok (STAI Terpadu Yogyakarta, 2021)
Qualified human resources will lead educational institutions to achieve their goals easily. This paper was written to know the concept of developing human resource management is, and the process of developing human resource management in Islamic educational institutions is. The author uses a qualitative approach to the type of literature (library research). The stages of the research that the author did were collecting research materials, reading literature, making small notes, processing the readings into research data. After analyzing the results obtained, among others: The concept of human resource management development is an activity of planning, coordinating, implementing, and evaluating. The process of developing human resource management includes education, training, and self-development. In more detail the process of developing human resources through, first: by conducting a needs diagnosis, second: conducting problem design, program design, participation design, educational calendar design, individual needs design, a group needs design, time design, procedure, and evaluation, third: the implementation process, and finally carry out the evaluation.